Development and Characterization of a Molecularly Imprinted Polymer for the Selective Removal of Brilliant Green Textile Dye from River and Textile Industry Effluents - Luna Quinto, Miguel; Khan, Sabir [UNESP]; Vega-Chacón, Jaime; Mortari, Bianca [UNESP]; Wong, Ademar [UNESP]; Taboada Sotomayor, Maria Del Pilar [UNESP]; Picasso, Gino (MDPI, 2023)
In this paper, we present an alternative technique for the removal of Brilliant Green dye (BG) in aqueous solutions based on the application of molecularly imprinted polymer (MIP) as a selective adsorbent for BG. The MIP was prepared by bulk radical polymerization using BG as the template; methacrylic acid (MAA) as the functional monomer, selected via computer simulations; ethylene glycol dimethacrylate (EGDMA) as cross-linker; and 2,2′-azobis(2-methylpropionitrile) (AIBN) as the radical initiator. Scanning electron microscopy (SEM) analyses of the MIP and non-molecularly imprinted polymer (NIP)—used as the control material—showed that the two polymers exhibited similar morphology in terms of shape and size; however, N2 sorption studies showed that the MIP displayed a much higher BET surface (three times bigger) compared to the NIP, which is clearly indicative of the adequate formation of porosity in the former. The data obtained from FTIR analysis indicated the successful formation of imprinted polymer based on the experimental procedure applied. Kinetic adsorption studies revealed that the data fitted quite well with a pseudo-second order kinetic model. The BG adsorption isotherm was effectively described by the Langmuir isotherm model. The proposed MIP exhibited high selectivity toward BG in the presence of other interfering dyes due to the presence of specific recognition sites (IF = 2.53) on its high specific surface area (112 m2/g). The imprinted polymer also displayed a great potential when applied for the selective removal of BG in real river water samples, with recovery ranging from 99 to 101%.
Keywords: adsorption; Brilliant Green; density-functional theory; kinetics; molecularly imprinted polymer; selective recognition; smart polymer; triphenylmethane dye; water treatment